Recommendations for the management of ST elevation myocardial infarction after reperfusion - Britto, Frank W. (2025)
The management of ST-segment elevation acute myocardial infarction after reperfusion involves critical decisions for patients with multivessel disease (MVD), acute heart failure, and left ventricular (LV) thrombus. Complete revascularization of non-culprit lesions ≥70% is recommended during the initial intervention or within the first 19 days, particularly in stable patients. Coronary artery bypass grafting is indicated for high-risk anatomies or complex lesions following a successful coronary intervention, where a hybrid strategy combines percutaneous intervention with surgery, with timing adjusted based on whether a stent was implanted. Post-infarction heart failure is common (28-31%) and requires urgent treatment. Continuous monitoring and prompt intervention can reduce complications. In cases of shock or mechanical complications, an intra-aortic balloon pump and inotropic support may be necessary. Right ventricular infarction is managed with volume support, urgent revascularization, and, if needed, pharmacological support or pacing. LV thrombus, which is more common in previous infarcts with LVEF <50%, requires early diagnosis through echocardiography and/or tomography, along with early anticoagulation, preferably with warfarin, considering triple therapy in cases of high thrombotic risk. This manuscript presents recommendations aimed at optimizing prognosis through early and personalized interventions based on the most recent evidence.